Abciximab as a bridging strategy to overcome morphine–prasugrel interaction in STEMI patients. (24th July 2016) - Siller‐Matula, Jolanta M.; Specht, Simon; Kubica, Jacek; Alexopoulos, Dimitrios; De Caterina, Raffaele; Hobl, Eva‐Luise; Jilma, Bernd; Christ, Günter; Lang, Irene M.
Abstract : Objective: The present study investigated whether the glycoprotein (GP)IIb/IIIa receptor blocker abciximab might be a successful bridging strategy to achieve adequate levels of platelet inhibition rapidly in cases where prasugrel is used in morphine‐pretreated ST‐elevation myocardial infarction (STEMI) patients. Methods: In a prospective observational cohort study, 32 patients presenting with STEMI were given prasugrel at a loading dose of 60 mg. Patients were stratified into four groups, according to morphine and/or abciximab use. Adenosine diphosphate (ADP)‐induced platelet aggregation was measured at four time points: at baseline, and at 2 h, 1 day and 2 days after prasugrel loading. Results: Morphine use was associated with a three‐fold higher level of ADP‐induced platelet aggregation 2 h after prasugrel loading compared with no morphine/no abciximab ( P = 0.019). However, when abciximab was infused in the catheterization laboratory, the effect of morphine on ADP‐induced platelet aggregation disappeared ( P = 0.884). This interaction was also seen in the presence of high on‐treatment platelet reactivity (HTPR) at 2 h; while HTPR was seen in 88% of morphine users/no abciximab users, it was found in only 17–20% in the three other groups ( P = 0.003). The effect of morphine disappeared by day 1 – 2. Conclusion: The infusion of the GPIIb/IIIa receptor blocker abciximab allows immediate and efficient platelet inhibition in STEMI patients concomitantly receiving the oral ADP receptor blocker prasugrel and morphine.